A review of leakage detection strategies for pressurised pipeline in steady-state. (January 2020) - Zaman, Dina; Tiwari, Manoj Kumar; Gupta, Ashok Kumar; Sen, Dhrubjyoti
Highlights: Comprehensive classification of steady-state leak detection methods is presented. Features of devices and computational tools are used as classification standards. Generalized frameworks developed for model and data driven software-based methods. Hybrid methods is more efficient in terms of higher accuracy and lesser error. Integrity management is crucial for leakage control and prevention in pipeline. Abstract: Pipeline and pipe networks are the most environmentally sustainable and energy-efficient means for transportation and distribution of fluids of high social and commercial value like drinking water, oil, and natural gas. Integrity management of the pipeline through leak prevention and early leak detection is crucial for their continuous operation and also to prevent the increase in energy burden and carbon emissions. The present study focuses on the performance-oriented critical evaluation of various leak detection approaches proposed for pressurised pipeline carrying different types of fluids. Basic leak hydraulics and effective leak management strategies that facilitate leak prevention are briefly discussed. Literature review reveals the availability of an overwhelming range of leak detection methods with different technicality as well as applicability. Several different mathematical techniques and hydraulic tools have also been utilised in the proposed methods, which makes it rather challenging to evaluate all of them on a common platform and impractical to assess their technical capabilities and limitations. A comprehensive classification of the most popular steady-state based leak detection methods is carried out, based on the core methodology utilised in each technique and without emphasizing on their individual technical detailing. This type of systematic classification and evaluation of leak detection approaches is deemed to be more useful for field applications by water utility personnel. Methods developed by combining two or more diverse techniques or processes have demonstrated to be more successful in leak localization, and such hybrid methods should be further developed for future beneficial use.